Antibacterial and antibiofilm effect of silver and gold nanoparticles in Uropathogenic Escherichia coli - Rini Purbowati; Sugiharto; Agusniar Furkani Listyawati; Masfufatun; Lusiani Tjandra; Noer Kumala Indahsari (The East Java Biological Society, 2022)
Nosocomial infections of the urinary tract are the most common nosocomial infections. Infectious diseases currently pose a life threatening due to the increasing phenomenon of infectious agent resistance. One of the factors known to cause resistance to broad-spectrum antimicrobials agent is the susceptibility to biofilm formation. The use of silver nanoparticles (NPs) is now regarded as one of the most promising strategies to target infections associated with biofilms. This study aims to determine the application of nanotechnology in the form of metal nanoparticles in targeting the formation of biofilms on infectious agents. The antibacterial and antibiofilm activity test was performed on a 96-well microtiter plate on uropathogenic Escherichia coli (UPEC) at concentrations of 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 ppm. The results showed the addition of silver and gold nanoparticles at different concentrations affected and inhibited the growth of UPEC and prevented the formation of biofilms, as indicated by a decrease in the OD value. In conclusion, silver and gold nanoparticles have antibacterial and antibiofilm effects on UPEC.